Cross-national correlations of quantifiable societal health with popular religiosity and secularism in the prosperous democracies: a first look - Paul, Gregory S. (The journal of religion & society, 2005)
Large-scale surveys show dramatic declines in religiosity in favor of secularization in the developed democracies. Popular acceptance of evolutionary science correlates negatively with levels of religiosity, and the United States is the only prosperous nation where the majority absolutely believes in a creator and evolutionary science is unpopular. Abundant data is available on rates of societal dysfunction and health in the first world. Cross-national comparisons of highly differing rates of religiosity and societal conditions form a mass epidemiological experiment that can be used to test whether high rates of belief in and worship of a creator are necessary for high levels of social health. Data correlations show that in almost all regards the highly secular democracies consistently enjoy low rates of societal dysfunction, while pro-religious and anti-evolution America performs poorly.